The Effect of Local Wisdom-Based Storytelling Methods on the Speaking Skills of 4-5 Year Old Children at Kasih Ibu Labuan Lelea Kindergarten - Nadia Mokodompit; Durrotunnisa Durrotunnisa; Amrullah Amrullah; Nurhayati Nurhayati (Journal of Educational Sciences, 2026)
Early Childhood Education (PAUD) is an important foundation in children's language, social, and cognitive development. This study aims to determine the effect of local wisdom-based picture storytelling methods on the speaking skills of children in Group A at Kasih Ibu Labuan Lelea Kindergarten. The study used a quantitative approach with a one-group pretest–posttest experimental design. The research subjects consisted of 15 children, and data were obtained through observation, documentation, and teacher interviews. Data analysis was performed descriptively and inferentially using a paired sample t-test. The results showed an increase in children's speaking skills after the treatment. The average speaking ability increased, with a significant increase in the number of children in the Very Good Development and Expected Development categories, while the Starting to Develop and Not Yet Developed categories decreased. Statistical analysis showed that the t-count value was greater than the t-table, which confirmed the significant effect of the storytelling method on children's speaking skills. In conclusion, the application of the local wisdom-based picture storytelling method is effective in improving the speaking skills of early childhood. This method not only enriches vocabulary but also trains children to answer questions, recognize story characters, and build confidence in expressing themselves verbally.